Lpar2b Controls Lateral Line Tissue Size by Regulating Yap1 Activity in Zebrafish - Wang, Xueqian; Hou, Haitao; Song, Kaida; Zhang, Zhiqiang; Zhang, Shuqiang; Cao, Ying; Chen, Liming; Sang, Qing; Lin, Fang; Xu, Hui (Frontiers in Molecular Neuroscience, 2018)
LPA signaling plays important roles during cell migration and proliferation in normal and pathological conditions. However, its role during sensory organ development remains unknown. Here we show a LPA receptor Lpar2b is expressed in the posterior lateral line primordium (pLLP) and mechanosensory organs called neuromasts (NMs) in zebrafish embryos. Lpar2b loss-of-function significantly reduces the number of NMs and hair cells in the posterior lateral line (pLL). Further analysis reveals that Lpar2b regulates the patterning and organ size of the pLLP. Interestingly, we show that knocking down a Hippo effector Yap1 phenocopies the result of Lpar2b depletion, and Lpar2b regulates the phosphorylation and activity of Yap1 in the pLLP. Importantly, a phosphorylation-resistant Yap1 rescues pLLP organ size and NM number in Lpar2b-depleted embryos. Our results indicate Lpar2b controls the sensory organ size and NM number by regulating Yap1 activity in the lateral line system.